2017
DOI: 10.7717/peerj.3664
|View full text |Cite
|
Sign up to set email alerts
|

The effects of allogenic stem cells in a murine model of hind limb diabetic ischemic tissue

Abstract: BackgroundDiabetes is one of the major risk factors for peripheral arterial disease. In patients in whom surgery cannot be performed, cell therapy may be an alternative treatment. Since time is crucial for these patients, we propose the use of allogenic mesenchymal cells.MethodsWe obtained mesenchymal cells derived from the fat tissue of a healthy Sprague-Dawley rat. Previous diabetic induction with streptozotocin in 40 male Sprague-Dawley rats, ligation plus left iliac and femoral artery sections were perform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In accordance with other reported preclinical studies [2, 19, 59, 63], in our experiments, AMSC injection was followed by an increase in neovascularization. We have been able to assess the significant increase as early as 1 week after treatment.…”
Section: Discussionsupporting
confidence: 79%
“…In accordance with other reported preclinical studies [2, 19, 59, 63], in our experiments, AMSC injection was followed by an increase in neovascularization. We have been able to assess the significant increase as early as 1 week after treatment.…”
Section: Discussionsupporting
confidence: 79%
“…The TACT (Therapeutic Angiogenesis using Cell Transplantation) study first demonstrated the efficacy and safety of autologous BM-MNC transplantation for critical limb ischemia (CLI) [49], but subsequent meta-analysis of 10 randomized controlled trials showed no significant differences in major amputation rates, survival, or amputation-free survival between patients treated with BM-MNCs or placebos [50]. In recent clinical studies, transplantation of MSCs has gained interest and is the most widely examined as a new strategy for vascular diseases in both humans and animal models [51]. According to ClinicalTrials.gov, to date (March 2020), 23 clinical trials were registered to investigate therapeutic effects of MSC transplantation on CLI.…”
Section: Discussionmentioning
confidence: 99%
“…There were no differences among functional parameters in patients undergoing intramuscular vs. intraarterial cell supply. Preclinical (66) and clinical (67) data from our group substantiate these remarks; nevertheless, our humble experience indicates that the route of administration depends on the type and the dose of cell to be administered. Deciphering how stem cells manage the countless signals required for revascularization will improve CLI recovery, Qadura et al (31) proposed a combination delivery of multiple cell types within supportive bioengineered matrices as a new therapeutic strategy to target CLI.…”
Section: Clinical Trials For Pad Ischemia and CLImentioning
confidence: 72%
“…Regarding the use of MSCs as a cell-based therapy for CLI, recent data suggest that the therapeutic effects of these cells in ischemic pathologies are due to the secretion of angiogenic molecules to bioactive levels and their ability to restore the microenvironment of the damaged area (70). In preclinical studies, the administration of autologous, allogeneic, and xenogeneic MSCs derived from various sources such as bone marrow, umbilical cord blood, fetal membrane and adipose tissue have been shown to be beneficial in rat and mouse models with lower limb ischemia (66). Subsequently, several phase I/IIa clinical trials have been assayed in a limited number of patients to demonstrate the safety and feasibility of MSCs obtained from different sources (7175).…”
Section: Clinical Trials For Pad Ischemia and CLImentioning
confidence: 99%